Environmentalists and their conflicts with Energy Justice – Concept of "Power-Environ" in the Athirappilly HEPP in Kerala. (June 2019) - Jayapalan, C.; Ganesh, L.S.
Abstract: This paper describes how a green energy surplus region changed over the years to a thermal energy-mix, driven by environmentalist forces' strong opposition to Hydro-Electric Power Projects (HEPPs) in Kerala, India. The specific instance of the proposed Athirappilly HEPP is discussed against the background of the opposition of environmentalists and other sympathetic associations. The strong opposition to HEPPs in specific local contexts has led to increased emissions in other places. The tenets of Energy Justice – distributional, procedural, recognition and cosmopolitan – have been challenged by the environmentalists' movement against the Athirappilly HEPP. The inherent conflicts between Environment Law and Climate Law on the one hand and the principles of Energy Justice and Law on the other are pointed out. The concept of "Power-Environ" is introduced and characterized, and its relation to Energy Justice and Law is explored in the policy context. The concept proposed here serves as a foundation for realizing parsimonious and effective representation of the opposition to HEPPs, and ushering Energy Justice and Law. The use of this concept, as an integrated whole founded on the principles of Energy Justice and Law, should facilitate balanced policy-making in the Energy sector, especially in India and hopefully across the world too. Highlights: Presents how a green energy-surplus region changed to a thermal energy- mix. A data-based, qualitative-analytical approach to examine a HEPP in India. Introduces the Power-Environ concept based on Principles of Energy Justice and Law. A parsimonious and effective visual-conceptual representation of Power-Environ. Facilitates balanced policy-making in the Energy sector.